Animated VR and 360-degree VR to assess and train team sports decision-making: a scoping review - Jia, Y.; Zhou, X.; Yang, J.; Fu, Q. (Frontiers in Psychology, 2024)
Introduction: In team sports, athletes` ability to make quick decisions plays a crucial role. Decision-making proficiency relies on the intricate balance of athletes` perceptual and cognitive abilities, enabling them to assess the competitive environment swiftly and select the most appropriate actions from various options. Virtual reality (VR) technology is emerging as a valuable tool for evaluating and refining athletes` decision-making skills. This study systematically examined the integration of VR technology into decision-making processes in team sports, aiming to identify more effective methods for presenting and interacting with virtual decision-making systems, thus enhancing the evaluation and refinement of athletes` decision making abilities.